2012
DOI: 10.1186/1471-230x-12-109
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal fluctuations in PD1 and PD-L1 expression in association with changes in anti-viral immune response in chronic hepatitis B

Abstract: BackgroundControversy exists regarding the role of PD1 and its ligand PD-L1 in chronic hepatitis B infection. In some studies, persistent HBV infection has been attributed to high levels of PD-1 and PD-L1 expression on HBV-specific T-cells and antigen-presenting cells (APCs) respectively. Other studies revealed that the up-regulation of PD-1 and PD-L1 during an acute inflammation phase is required to offset increasing positive co-stimulatory signals to avoid severe damage by an over-vigorous immune response.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 22 publications
(26 reference statements)
3
23
1
Order By: Relevance
“…Longitudinal immunologic studies showed a decline of HBcAg-specific regulatory T cell (Treg) frequencies, associated with an increase in HBcAg-specific cytotoxic T lymphocyte (CTL) frequencies prior to the peak of the hepatitis flare [28][29][30], IL-10-producing regulatory B cell frequencies and serum IL-10 level peaked with the increase in viral load and decreased at the same time or shortly after the peak of ALT [31], large fluctuations in serum IFN-a and IL-8 concentrations with peak levels coinciding with a sharp increase in viral load preceding the onset of the hepatitis flare, and the increases in serum IFN-a and IL-8 promoted a pathway for the natural killer (NK)-cell mediated liver damage [32]. It was also shown that hepatitis flares were temporarily associated with high serum levels of INF-c inducible chemokines CXCL-9 and CXCL-10 [33], and that increase, peak and decline in the levels of the programmed cell death protein 1 (PD-1) and its ligand PD-L1 went parallel with the ascend, peak and decline of HBV-specific T cells and serum ALT levels [34]. Integrated together (Table 1), these findings suggest that hepatitis B flares are the results of dynamic changes of the innate and adaptive immune responses with HLA-I restricted, CTL mediated immune cytolysis of HBV antigen(s) expressing hepatocytes and its downstream apoptotic mechanisms [3,7].…”
Section: Pathogenesis Of the Hepatitis B Flarementioning
confidence: 95%
“…Longitudinal immunologic studies showed a decline of HBcAg-specific regulatory T cell (Treg) frequencies, associated with an increase in HBcAg-specific cytotoxic T lymphocyte (CTL) frequencies prior to the peak of the hepatitis flare [28][29][30], IL-10-producing regulatory B cell frequencies and serum IL-10 level peaked with the increase in viral load and decreased at the same time or shortly after the peak of ALT [31], large fluctuations in serum IFN-a and IL-8 concentrations with peak levels coinciding with a sharp increase in viral load preceding the onset of the hepatitis flare, and the increases in serum IFN-a and IL-8 promoted a pathway for the natural killer (NK)-cell mediated liver damage [32]. It was also shown that hepatitis flares were temporarily associated with high serum levels of INF-c inducible chemokines CXCL-9 and CXCL-10 [33], and that increase, peak and decline in the levels of the programmed cell death protein 1 (PD-1) and its ligand PD-L1 went parallel with the ascend, peak and decline of HBV-specific T cells and serum ALT levels [34]. Integrated together (Table 1), these findings suggest that hepatitis B flares are the results of dynamic changes of the innate and adaptive immune responses with HLA-I restricted, CTL mediated immune cytolysis of HBV antigen(s) expressing hepatocytes and its downstream apoptotic mechanisms [3,7].…”
Section: Pathogenesis Of the Hepatitis B Flarementioning
confidence: 95%
“…The fact that a PD-1 1 NK cell subset could be detected in only some of the subjects analyzed might be a result of latent chronic infections affecting these subjects (in this context it is of note that an increase in PD-1 1 lymphocyte numbers has been associated with hepatitis C virus, hepatitis B virus, and HIV infections). 6,7,[61][62][63] Although a correlation exists between the presence of PD-1 1 NK cells and HCMV infection, phenotypic analysis of PD-1 1 NK cells showed that NKG2C (the expression of which is associated to HCMV infection) is not preferentially expressed by PD-1 1 cells. However, similar to NKG2C 1 NK cells accumulating in response to HCMV infection, the PD-1 1 subset was almost exclusively composed of highly differentiated NKG2A 2 KIR 1 CD57 1 NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…The second step of the increased serum sPD-L1 levels, from immunotolerance (CHB-IT) to immunoactivation (CHB-IA), is in concordance with the positive correlation of the intrahepatic expressions of PD-1 and PD-L1 with liver inflammation in CHB [29,30]. Thus, the PD-1/PD-L1 axis, after immunoactivation, is served as an adaption of the host defense to minimize immunopathology [31].…”
Section: Discussionmentioning
confidence: 66%
“…In CHB-IA, NUC treatment was correlated with significantly higher serum sPD-L1 levels, which was strong and independent on the status of ALT in HBeAg-positive CHB-IA. However, the correlation in HBeAg-negative CHB-IA was not obvious, probably because such NUC-treated patients with adequate response is more like CHB-IC, in which the long-term remission of liver inflammation is trend to decrease the intrahepatic PD-L1 expression [29,30]. Indeed, the serum sPD-L1 levels showed a downward trend in CHB-IC in this study.…”
Section: Discussionmentioning
confidence: 68%